Starch, nitrite, and nitrate analysis in inspected and uninspected fresh pork sausages - Moraes, Gustavo Nunes de; Camargo, Gabriel Corrêa de; Santomauro, Rafael Alves; Sampaio, Aryele Nunes da Cruz Encide; Cézar, Camila Koutsodontis Cerqueira; Caron, Evelyn Fernanda Flores; Possebon, Fábio Sossai; Pereira, Juliano Gonçalves; Martins, Otávio Augusto (Food Science and Technology, 2025)
Fresh pork sausages are among the most consumed meat products in Brazil. However, in the informal market, they are more susceptible to fraud by adding prohibited ingredients, such as starch, or in amounts exceeding safe health limits. In this context, the present study quantified the concentrations of nitrite and nitrate and also investigated the presence of starch in samples of fresh pork sausages sold in the mesoregion of the municipality of Bauru, São Paulo, Brazil. A total of 40 samples were analyzed, including 30 from three different brands inspected by regulatory agencies and 10 uninspected. All food products analyzed were within the limits established by Brazilian legislation for starch (absence), nitrite, and nitrate (maximum of 150 and 300 mg/kg, respectively). The importance of consuming inspected food is emphasized, given the health risks posed by the consumption of products that do not comply with the hygienic-sanitary and production standards established by law.